Production of Aroma-Rich Extracts from Sardine Cooking Wastewaters - Resende, Daniela (2024)
Publisher Copyright: © The Author(s) 2024. Open access funding provided by FCT|FCCN (b-on). This research was funded by Project “MobFood—Mobilizing scientifc and technological knowledge in response to the challenges of the agri-food market” (POCI-01-0247-FEDER-024524), fnanced by ERDF, through PORTUGAL2020/COMPETE2020/Lisb@2020.